Peranan Aktivitas Urban Tourism Dan Minat Wisatawan Dalam Sport Tourism: Implikasi Bagi Pengembangan Bisnis Pariwisata Perkotaan - Sri Marini; Eka Saputra; Superwiratni (Program Studi Administrasi Bisnis, 2026)
The city of Bandung offers tourist attractions across various sectors, including natural, cultural, culinary, and shopping attractions. The objective of this study is to investigate the research focus: whether tourists’ interest in sports tourism activities promoted by various stakeholders impacts urban tourism activities. The research approach employs a qualitative approach using field research methods. The key informants in this study include internal informants—comprising fun run event organizers, the event’s main sponsor, and tourism and hospitality associations—as well as external informants consisting of 20 participants in the fun run sports tourism activity, both from outside the region and locally, who served as eligible sources to provide information regarding interest in sports tourism and urban tourism activities. Qualitative data analysis used in this study. The processes reduction, data display, and verification of data was conducted interactively. The research findings indicate that interest in sports tourism boosts tourist visits, has an impact on urban tourism activities, and has implications for the development of the urban tourism industry.